Strategi Komunikasi Pemasaran Melalui Media Sosial Instagram “Yo Dream Cake” Dalam Membentuk Brand Awareness - Kholistia Ulfa Khairiah; Ridho Syukri; Yuniza Aida (CV. ULIL ALBAB CORP, 2024)
Instagram is in great demand in this era in more effective marketing to boost sales. The aim of this research is to know marketing communication strategies through social media Yo Dream Cake by Dhea in shaping brand awareness on Instagram. This research method uses descriptive methods through a qualitative approach. Data collection techniques are with interviews, observations and documentation. The secondary data in this study is data obtained from Yo Dream Cake that is needed in connection with research such as the image of Instagram Yo dream Cake. The results of the research carried out known strategy of marketing communication among others with marketing through social media is Instagram by providing content, giveaway and video products to consumers, among other things with promotions, advertising, direct and personal sales, whileining the relationship with consumers Yo dream cake. However, in addition to using Instagram social media in marketing communication strategies, it is better to use other social media that can more widely market their services and products with other social networks, such as Facebook and the booming Tiktok. In addition to adding new customers, the addition of social media in marketing can support and help inining a well- executed and regular relationship with consumers.